The Silent Crisis: Economic Burden of Diagnosis for Genetic Diseases in Low- and Middle-Income Countries (LMICs) - Baig, Atif Amin; Hla Thein, Khin Hla; Mynt Htoo, Phone; Anwar, Khawar; Chopra, Hitesh; Shivani, (Scripta Medica, 2026)
Genetic disorders, although secondary to infectious and non-communicable diseases in the global health priority agenda, are an important drain, albeit ill-defined, on the economies of low- and middle-income countries (LMICs) and on their health resources. The economic costs of diagnosing a genetic disorder in these settings, both direct and indirect, are detailed in the narrative review. Direct costs include the significant expense of advanced molecular diagnosis, inadequate infrastructure and dependence on expensive foreign services, which are largely financed through catastrophic, out-of-pocket payments. Indirect costs include the prolonged and expensive “diagnostic odyssey,” the loss of productivity in patients and patients’ relatives and the costs to society of misdiagnosis and avoidable disability. This emergency can be addressed by investing in strategic local diagnostic capacity, task-shifting and innovative finance models to enable equal access to genomic medicine and to break the vicious cycle of health-related poverty in LMICs.